A direct assessment of refractive indices of nematic liquid crystals at broad VIS - MWIR range. Issue 5 (9th April 2018) - Miszczyk, Emilia; Morawiak, Przemysław; Mazur, Rafał; Mrukiewicz, Mateusz; Olifierczuk, Marek; Piecek, Wiktor; Raszewski, Zbigniew; Kula, Przemysław; Kędzierski, Jerzy; Zieliński, Jerzy; Harmata, Piotr
ABSTRACT: We developed an interference method for determination refractive indices of nematic liquid crystals in a broad electromagnetic spectrum. Values of ordinary and extraordinary refractive indices were measured in VIS (from 0.4 to 0.8 μm), NIR (from 0.8 to 1.4 μm), SWIR (from 1.4 to 3.0 μm) and at an edge of MWIR (from 3.0 to 4.2 μm) regions. The main task of this work was to develop the efficient and accurate interference method. The absolute error of these measurements is not higher than 0.02. The method was tested on two newly designed mixtures. The first one was a high birefringence liquid crystal mixture for the laser rangefinder, while the second one is intentionally prepared for breathalyser application. The mixture does not possess high absorption bands at 3.4 μm. To measure a dispersion of the refractive indices cells with various thicknesses and dielectric mirrors were prepared. The paper presents a theoretical discussion and experimental results. Graphical Abstract: